Examining the Lived Experience of Student Veterans Using Photovoice Methodology - (:unkn) unknown (My University, 2013)
The primary objective of this study was to understand the lived experience of student veterans using photovoice methodology. After returning from service veterans struggle most with school (Plach & Haertlein Sells, 2013). Student veterans experience difficulty in time management, and transitioning to student life (Radford, 2009). They spend more time working at jobs and caring for dependents than non-veteran students, but spend equivalent time studying. They perceive less engagement with faculty and campus support than their peers (NSSE, 2010). For many veterans, education is a primary occupation but there is dearth of data about their lived experience and factors that help or hinder their pursuit of educational goals. This study employed a qualitative research design using photovoice methodology (Wang & Burris, 1997) to gain such insight. Student veterans were recruited after obtaining Institutional Review Board approval and informed consent. After being trained in the photovoice methodology, participants were provided with cameras to capture aspects of their life that they wanted to convey regarding the transition process through photography. With their photographs as references, participants engaged in group discussions (audio recorded), and wrote narratives that they consider important to convey to multiple audiences including researchers, health promotion providers, university personnel and policy makers. These narratives conveyed lived experiences that reflect challenges experienced while attaining an education and factors that helped them to overcome such challenges. Narratives and discussion session transcripts were analyzed using thematic analysis and descriptive coding. Analysis lead to formulation of four themes: 1) reminiscence of past duty and reflections on military life, 2) transition from military to civilian student life, and 3) entry to a new stage of life and 4) university and community environment. Findings from this study can help researchers, health promotion providers, the higher education community, and policy makers to acknowledge the factors that challenge or support student veterans so that programs and services can be offered to assist them in attaining their educational goals.
Keywords: Advocacy; Lived Experience; Occupational Therapy; Photovoice; Student Veterans